2010
DOI: 10.21273/horttech.20.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Green Roof Plant Responses to Different Substrate Types and Depths under Various Drought Conditions

Abstract: Plants suitable for extensive green roofs must tolerate extreme rooftop conditions, and the substrates in which they grow must fulfill horticultural and structural requirements. Deeper substrates may retain more water for plants during dry periods, but will also weigh more, especially when near saturation. A study in central Pennsylvania was conducted to evaluate the influence of substrate type and depth on establishment of five green roof plants. Two stonecrops [white stonecrop (Sedum alb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 13 publications
(24 reference statements)
7
55
2
5
Order By: Relevance
“…General conclusions regarding depth agree with many previous studies on succulents, as well as herbaceous perennials and grasses (Benvenuti & Bacci, 2010;Dunnett, Nagase, & Hallam, 2008;Durhman et al, 2007;Thuring et al, 2010). Deeper media depths allow for greater diversity in plant material and generally encourage healthier plants with greater biomass.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…General conclusions regarding depth agree with many previous studies on succulents, as well as herbaceous perennials and grasses (Benvenuti & Bacci, 2010;Dunnett, Nagase, & Hallam, 2008;Durhman et al, 2007;Thuring et al, 2010). Deeper media depths allow for greater diversity in plant material and generally encourage healthier plants with greater biomass.…”
Section: Discussionsupporting
confidence: 88%
“…When 18 herbaceous perennials and grasses were evaluated in 10 cm of media without irrigation in Michigan, only four species (Allium cernuum, Coreopsis lanceolata, Opuntia humifusa, and Tradescantia ohiensis) still existed after three years (Monterusso, Rowe, & Rugh, 2005;Rowe, Monterusso, & Rugh, 2006). Other studies have shown similar results (Dunnett, Nagase, & Hallam, 2008;Durhman et al, 2006;Thuring, Berghage, & Beattie, 2010). In all of these studies, if irrigation had been available, then a greater number of species would have likely survived.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Early studies (Durhman et al, 2007;Lassalle, 1998) have also demonstrated that deeper substrate can retain more water, which allows plants to maintain a better physiological state when supplementary watering is restricted on green roofs. Therefore, deeper substrate tends to promote growth rate, survival and coverage of Sedums (Durhman et al, 2007;Thuring et al, 2010), and improves floral assemblage and species richness on green roofs (Olly et al, 2011 andRowe et al, 2012). Secondly, a smaller plant is less sensitive and more tolerant to drought stress than larger ones, because it usually uses less water (Blum, 2011).…”
Section: Relationships Between Substrate Depth and Plant Drought Tolementioning
confidence: 99%
“…Substrate depth generally range from 2 to 15 cm on extensive green roofs, limited by the dead load weight of many buildings. Green roof plants grown in deeper substrate tend to have better growth and higher biomass accumulation and survival (Durhman et al, 2007;Thuring et al, 2010;Nektarios et al, 2011;). Rowe et al (2012) studied the impacts of media depths on the succession of 25 succulents over a course of seven years and found that the number of species was reduced at a faster pace with shallower depths.…”
Section: Introductionmentioning
confidence: 99%